1986
DOI: 10.1007/bf00251051
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic ribbon populations in the pineal gland of the rhesus monkey (Macaca mulatta)

Abstract: Pinealocytes of rhesus monkeys that had been ovariectomized and given intramuscular injections of 250 micrograms estradiol-benzoate for 3 consecutive days tended to have more synaptic ribbons (SR) and exhibited a significantly greater size of ribbon fields (RF) compared to untreated animals. These data are consistent with hypotheses that pinealocyte function in primates is altered by hormonal imbalances and that the SR participates in this response. RF were positioned in various parts of the cytoplasm and alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…13. 15-17.25.26] and Primates [27][28][29]. in which appar ently the greatest numbers per unit area were found.…”
Section: Discussionmentioning
confidence: 99%
“…13. 15-17.25.26] and Primates [27][28][29]. in which appar ently the greatest numbers per unit area were found.…”
Section: Discussionmentioning
confidence: 99%
“…In the rhesus monkey (Macaca mulatta) SRP numbers were significantly increased after ovariectomy and estradiol benzoate treatment compared to untreated controls (McNulty et al, 1986). A similar observation was made 2 and 3 weeks after orchidectomy in rats (Karasek, 1976).…”
Section: Discussionmentioning
confidence: 55%
“…Synaptic ribbons in the pinealocyte cytoplasm, so often reported in other animals, e.g., rliesus monkey (McNulty et al, 1986), have not been observed in the vampire. At present it cannot be argued effectively whether these organelles are altogether absent in Desmodus or whether their lack represents a physiological state in which they remain unexpressed.…”
Section: Innervationmentioning
confidence: 92%